People Rely Less on Consumer Reviews for Experiential than Material Purchases - Dai, Hengchen; Chan, Cindy; Mogilner, Cassie (Journal of Consumer Research, 2020)
An increasingly prevalent form of social influence occurs online where consumers read reviews written by other consumers. Do people rely on consumer reviews differently when making experiential purchases (events to live through) versus when making material purchases (objects to keep)? Though people often use consumer reviews both when making experiential and material purchases, an analysis of more than six million reviews on Amazon.com and four laboratory experiments reveal that people are less likely to rely on consumer reviews for experiential purchases than for material purchases. This effect is driven by beliefs that reviews are less reflective of the purchase’s objective quality for experiences than for material goods. These findings not only indicate how different types of purchases are influenced by word of mouth, but also illuminate the psychological processes underlying shoppers’ reliance on consumer reviews. Furthermore, as one of the first investigations into how people choose among various experiential and material purchase options, these findings suggest that people are less receptive to being told what to do than what to have.